2003
DOI: 10.1093/pch/8.6.357
|View full text |Cite
|
Sign up to set email alerts
|

Death and bereavement in a paediatric intensive care unit: Parental perceptions of staff support

Abstract: OBJECTIVES: To determine which staff behaviours and interventions were helpful to a family who had a child die in the intensive care unit (ICU) and which behaviours could be improved. METHODS: Families whose child died six to 18 months earlier were invited to participate. Families whose child's death involved a coroner's inquiry were excluded. Family members were interviewed by a grief counselor, and completed the Grief Experience Inventory Profile and an empirically designed questionnaire. RESULTS: No family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 27 publications
4
43
0
2
Order By: Relevance
“…Eleven of the 15 articles addressed parents' perceptions of staff attitude or affect at some point during the child's death (Abib El Halal et al., ; Bright et al., ; Brooten et al., ; Heller & Solomon, ; James & Johnson, ; Macnab et al., ; Meert et al., , ; Meyer et al., ; Neidig & Dalgas‐Pelish, ; Widger & Picot, ). Of these, seven articles identified aspects of staff affect or attitudes that were viewed as helpful by parents.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven of the 15 articles addressed parents' perceptions of staff attitude or affect at some point during the child's death (Abib El Halal et al., ; Bright et al., ; Brooten et al., ; Heller & Solomon, ; James & Johnson, ; Macnab et al., ; Meert et al., , ; Meyer et al., ; Neidig & Dalgas‐Pelish, ; Widger & Picot, ). Of these, seven articles identified aspects of staff affect or attitudes that were viewed as helpful by parents.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, seven articles identified aspects of staff member attitude and affect that were unhelpful or detrimental to parents' experiences (Abib El Halal et al., ; Bright et al., ; Brooten et al., ; Macnab et al., ; Meert et al., ; Meyer et al., ; Neidig & Dalgas‐Pelish, ). Parents consistently identified a cold, non‐caring and clinical demeanour as particularly unhelpful, leading to increased emotional pain, and they often identified medical staff as most likely to display such an attitude, especially in the PICU (Abib El Halal et al., ; Bright et al., ; Macnab et al., ; Meert et al., ). Bright and colleagues (), in their study of bereaved parents' interactions with medical staff, found that the pain and distress caused by cold and clinical physicians remained with parents for years after the child's death and gave the impression that the medical staff did not care about the deceased children or their families.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations